The 2nd European race walking conference - Drake, A.; Richards, I. (New Studies in Athletics, 2013)
Kurzzusammenfassung der Beiträge der 2. Europäische Konferenz Sportgehen: Murta, P.: The training of Ana Cabecinha - from age 11 to the London Olymics Brown, M.: Performance management of the Olympic triathlon champion Alistair Brownlee Kivimaki, M.: Race walking development initiatives in Finland Hanley, B.: Biomechanics and the rules of race walking Der Beitrag veröffentlicht auch die "Conference Declaration 2012".